SWOT Analysis Of Potential Regional Original Income And Development Of Bakar Tongkang Bagansiapiapi Cultural Tourism - Nyoto Nyoto; Irwan Effendi; Nicholas Renaldo (Politeknik APP Jakarta, 2024)
The barge burning event go gue cap lak is a local tradition of the Chinese community in Bagansiapiapi. This event is a cultural ritual event for the people of the east coast of Sumatra Island. The event has had an economic effect on the people of Bagansiapiapi City at large. The research was conducted by observation, unstructured in-depth interviews, and literature study. The Baking Barge go gue cap lak tradition event was analyzed from the perspective of the potential local revenue generated on the economic activity conditions of the people of Bagansiapiapi City, namely by using a SWOT analysis technique (strengths, weaknesses, opportunities, and threats) systematically. The barge-burning cultural event is a unique and specific cultural event for the people of the east coast of Sumatra. The barge-burning cultural event is able to attract thousands of local and foreign tourists. The barge-burning cultural event has a great economic effect on local revenue of the Rokan Hilir district government.